The Hermeneutics of Information in the Context of Information Technology. - Diamante, Oscar R. (KRITIKE: An Online Journal of Philosophy)
The digital revolution has drawn us into the "information age," and information has become central in our discourses of communication, economics, socio-cultural studies, etc. A look into the historical evolution of the concept of information reveals its assimilation into the technical and positivistic orientation, largely shaped by the technically- and mathematically-oriented information theory and the analytic philosophy of information. A hermeneutical view of information is to bring information into the phenomenon of understanding from the perspective of philosophical hermeneutics developed by Hans-Georg Gadamer. Philosophical hermeneutics is not concerned with the art of interpretation, as what the traditional hermeneutics characteristically was, but with understanding as the fundamental mode of being of the human person. To view information within the realm of understanding, or to unfold its hermeneutic dimension, it is necessary to challenge its objectified and reified conception. To achieve this, an elucidation of the essential features of hermeneutic understanding, like its interpretive nature and linguisticality, shall take the aspect of engaging the phenomenon of information in the context of information technology. A relevant conclusion shall reveal the possibility of reintegrating information into the fundamental orientation of human praxis as coming to an understanding.